Implications of Natural Science Physics Materials and Characteristics of Net Generations for 21st Century Competency Development - Meili Yanti (Jurnal Multidisiplin Madani, 2022)
The changes facing the world are complex and require new competencies to deal with them. The entry of the 21st century forces all parties to seek to develop themselves in order to compete in the international market. Also with Education, especially in Indonesia. This is the view for the teacher, the government and the students themselves. So, the purpose of this article is to provide an explanation of the role characteristics of Net Generations as students faced by teachers and the depth and breadth of KD Curriculum 2013 to 21st century competencies of the learners. The analytical method used is documentation study, by collecting documents about PISA 2015 and Curriculum syllabus 2013. The analysis results show that the depth and extent conducted on KD 3.4 and 4.4 on temperature and heat topics obtained that the material has covered all basic competence demands. But not enough if you want to develop literacy science and technology of learners so less recommended to help improve the competence of the 21st century